Incidence and Predictors of Serological Treatment Response in Early and Late Syphilis Among People Living With HIV. (30th November 2018) - Spagnuolo, Vincenzo; Poli, Andrea; Galli, Laura; Nozza, Silvia; Bossolasco, Simona; Cernuschi, Massimo; Maillard, Myriam; Hasson, Hamid; Gianotti, Nicola; Guffanti, Monica; Lazzarin, Adriano; Castagna, Antonella
Abstract: Background: Few studies have investigated predictors of serological response to syphilis treatment in people living with HIV (PLWH). Methods: This was a retrospective, longitudinal study on PLWH who were diagnosed with and treated for syphilis who had an assessable serological response between January 2004 and June 2016. Serological treatment response (TR) was defined as a ≥4-fold decline in rapid plasma reagin (RPR) titers or a reversion to nonreactive (if RPR ≤1:4 at diagnosis) 12 months after treatment for early syphilis and 24 months after treatment for late syphilis. Factors associated with a TR were assessed with multivariate Cox proportional hazard models for recurrent events. Results: A total of 829 episodes of syphilis (686 early, 143 late) in 564 patients were recorded. TR was observed in 732 (88%) syphilis episodes. The proportion of TR differed between early and late syphilis (89% vs 83%, respectively; P = .045). For early syphilis, TR was associated with a higher nadir CD4+ cell count (adjusted hazard ratio [AHR], 1.06; P = .029), an RPR titer >1:32 at diagnosis (AHR, 1.26; P = .009), secondary syphilis (AHR, 1.29; P = .008), and cases of syphilis diagnosed in more recent calendar years (AHR, 1.36; P < .0001). In late syphilis, TR was more likely to occur for first infections (AHR, 1.80; P = .027), for episodes that occurred in more recent years (AHR, 1.62; P = .007), and for RPR titers >1:32 at diagnosis (AHR, 2.04; P = .002). TR was not associated with the type of treatment regimen in early and late syphilis. Conclusions: Higher RPR titers at diagnosis and a diagnosis of syphilis that was made in more recent years were associated with TR in early and late syphilis.